Polyphasic characterisation of Burkholderia cepacia complex species isolated from children with cystic fibrosis - Vicenzi, Fernando José (Mem Inst Oswaldo Cruz, 2016)
Cystic fibrosis (CF) patients with Burkholderia cepacia complex (Bcc) pulmonary infections have high morbidity and mortality. The aim of this study was to compare different methods for identification of Bcc species isolated from paediatric CF patients. Oropharyngeal swabs from children with CF were used to obtain isolates of Bcc samples to evaluate six different tests for strain identification. Conventional (CPT) and automatised (APT) phenotypic tests, polymerase chain reaction (PCR)-recA, restriction fragment length polymorphism-recA, recAsequencing, and matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) were applied. Bacterial isolates were also tested for antimicrobial susceptibility. PCR-recA analysis showed that 36 out of the 54 isolates were Bcc. Kappa index data indicated almost perfect agreement between CPT and APT, CPT and PCR-recA, and APT and PCR-recA to identify Bcc, and MALDI-TOF and recAsequencing to identify Bcc species. The recAsequencing data and the MALDI-TOF data agreed in 97.2% of the isolates. Based on recA sequencing, the most common species identified were Burkholderia cenocepacia IIIA (33.4%),Burkholderia vietnamiensis (30.6%), B. cenocepaciaIIIB (27.8%), Burkholderia multivorans (5.5%), and B. cepacia (2.7%). MALDI-TOF proved to be a useful tool for identification of Bcc species obtained from CF patients, although it was not able to identify B. cenocepacia subtypes.